4CPS-016 Predictive performance of glomerular filtration rate equations based on cystatin c, creatinine and their combination in critically ill patients. Issue 1 (23rd March 2023) - Albanell, M; Bastida, C; Marcos-Fendian, Á; Escolà, A; Mercandal, J; Castro, P; Soy, D
Abstract : Background and Importance: Twenty-four hour urine creatinine clearance (24h-ClCr) remains the gold-standard for estimating glomerular filtration rate (GFR) in critically ill patients; however, it has several drawbacks. Serum creatinine (SCr) is the most frequently used parameter to estimate GFR, however, Cystatin-C (CystC) may reflect GFR changes earlier than SCr. Aim and Objectives: To assess the performance of equations based on SCr, CystC, and their combination (SCr-CystC) for estimating GFR in critically ill patients in comparison to 24h-ClCr. Material and Methods: Retrospective, observational study in a tertiary-care hospital (May 2020 to July 2022). Patients with CystC, SCr and 24h-ClCr measurements within ± 2 days were included. Altered thyroid status and corticosteroids use for >5 days were recorded, as both can alter CystC values. 24h-ClCr was considered the reference method. GFR was estimated using SCr-based equations: CKD-EPI-Cr and Cockcroft-Gault (CG); CystC-based equations: CKD-EPI-CystC and CAPA; and Cr-CystC-based equations: CKD-EPI-Cr-CystC. Bland-Altman plots were used to compare GFR estimations with 24h-ClCr. Pearson´s correlation coefficients and concordance correlation coefficients (CCC) were calculated. Bias was assessed as (estimated GFR – 24h-ClCr); and precision as the SD of bias. Further analysis was performed with stratified data into 24h-CrCl<60mL/min/1.73m 2, 60-130mL/min/1.73m 2 and ≥130 mL/min/1.73m 2 . Results: We included 275 measurements, corresponding to 186 patients. Mean (SD) SCr, CystC and 24h-ClCr were 1.3 (1.1) mg/dL, 1.8 (1.2) mg/L, and 77.0 (57.7) mL/min, respectively. The influence of altered thyroid status (N=22) and corticosteroids therapy (N=64) on CystC values was statistically significant (p:0.0138 and p<0.000, respectively); however, as box-plot were overlapped, we did not exclude them from the analysis. Bland-Altman plots are shown in figure 1 . In the overall population, CKD-EPI-Cr equation showed the lowest bias (2.6) and best precision (33.1). In patients with 24h-CrCl <60mL/min/1.73m 2 (N=124), CystC-based equations showed the lowest bias (<3.0) and CKD-EPI-Cr-CystC was the most accurate (13.6). In the subgroup of 60 ≤24h-CrCl <130 mL/min/1.73m 2 (N=100), CKD-EPI-Cr-CystC was the most precise (20.9). However, in patients with 24h-CrCl ≥ 130mL/min/1.73m 2 (N=51), CystC-based equations underestimate GFR, while CG overestimates it (22.8). CKD-EPI-Cr-CystC obtained the highest Pearson´s coefficient (0.742) and CKD-EPI-Cr the highest CCC (0.785). Conclusion and Relevance: Our study showed no evidence of superiority of any equation over others for all evaluated parameters. CystC-based equations were less biased in individuals with impaired renal function (GFR<60 mL/min/1.73m 2 ), CKD-EPI-Cr-CystC performed properly in GFR from 60-130mL/min/1.73m 2 and CG in patients >130 mL/min/1.73m 2 . References and/or Acknowledgements: Conflict of Interest: No conflict of interest